Performing Legitimacy in Irregular Criminal Justice: Lessons from the People’s Tribunals - Aaron Fichtelberg (International Journal of Law, Social Science, and Humanities, 2026)
This paper examines the so-called “People’s Tribunals” in terms of the concept of sociological legitimacy. By examining critical responses to the Russell Tribunal (established to prosecute those responsible for the war in Vietnam), the article argues that there are two primary objections: the positivist critique and the procedural critique. The former argues that all law originates in the state. The second is that people’s tribunals are procedurally unjust. The paper argues that the normative expectations of putatively legal institutions, principles of due process and substantive justice function as tools for irregular institutions to establish their authority as do more trivial behaviors within the courtroom itself.